Factors Influencing the Relationship Between the Dose of Amlodipine Required for Blood Pressure Control and Change in Blood Pressure in Hypertensive Cats. (22nd September 2016) - Bijsmans, E.S.; Doig, M.; Jepson, R.E.; Syme, H.M.; Elliott, J.; Pelligand, L.
Abstract : Background: Hypertension is a common problem in elderly cats. In most cats, systolic blood pressure (SBP) of <160 mmHg is achieved in response to amlodipine besylate at either 0.625 or 1.25 mg q24h. The individual cat factors determining dose requirement dose have not been explored. Aims: To determine whether individual cat factors influence the dose of amlodipine required to achieve adequate blood pressure control and to determine whether factors other than the prescribed dose of drug alter the achieved plasma amlodipine concentrations. Methods: Fifty‐nine hypertensive cats that required 0.625 mg (A) and 41 cats that required 1.25 mg (B) amlodipine to reach a target SBP of <160 mmHg were identified, and plasma amlodipine concentrations were determined. Comparisons were made between groups, and multivariable linear regression models were performed to investigate predictors of antihypertensive response. Results: Cats that required a greater dose of amlodipine had significantly higher SBP at diagnosis of hypertension (A: (median [25th, 75th percentile]) 182 [175, 192] mmHg; B: 207 [194, 217] mmHg, P < .001), but comparable blood pressure was achieved after treatment. Plasma amlodipine concentrations were directly related to the dose of amlodipine administered. At diagnosis, cats in group B had significantly lower plasma potassium concentration (A: 4.1 [3.8, 4.5]; B: 3.8 [3.6, 4.2] mEq/L, P < .01). Weight did not differ between groups. The decrease in SBP was directly and independently associated with the SBP at diagnosis and the plasma amlodipine concentration. Conclusions and Clinical Importance: Cats with higher blood pressure at diagnosis might require a greater dose of amlodipine to control their blood pressure adequately. Differences in amlodipine pharmacokinetics between cats do not seem to play a role in the antihypertensive response.